Mechanically induced phase transformations of the sigma phase of nanograined and of coarse-grained near-equiatomic FeCr alloys - Costa, B. F. O. (2006)
A coarse-grained tetragonal sigma phase [sigma]-Fe0.54Cr0.46, prepared from an as-cast alloy, and a nanocrystalline [sigma]-Fe0.52Cr0.48 phase were ball-milled in argon in a Fritsch P0 ball-mill at different vibration amplitudes. X-ray diffraction evidences solely a gradual transformation of the sigma phases into bcc phases. Room-temperature Mössbauer spectroscopy shows further the presence of a non-magnetic phase which remains non-magnetic at least down to 35 K. It is attributed to an amorphous phase whose formation is favoured at grain boundaries by oxygen in such milling conditions. Possible explanations of the different final structures reported in the literature in high-energy ball-milled near-equiatomic Fe-Cr alloys are discussed.